Plasmon Properties of Polydisperse Aluminum Nanoparticles Produced in Spark Discharge - Vershinina, Olesya; Lizunova, Anna; Khramov, Egor; Filalova, Emiliia; Sanatulina, Arina; Novoselov, Artem; Nouraldeen, Messan; Malo, Dana; Kameneva, Ekaterina; Kerechanina, Mariia; Tokunov, Yuri; Ivanov, Victor (Applied Science and Engineering Progress, 2025)
Nanoscale aluminum is a promising material for ultraviolet (UV) plasmonics for improving biosensors, light sources, and solar cells. Our study proposes a technique for producing aluminum nanoparticles with controlled average sizes using a gas discharge by adjusting the energy density released on the electrode surfaces. The key objective of this research is to investigate the impact of the variation in the dimensions of the inner and outer diameters of the electrodes on the synthesis efficiency, size distribution, and optical properties of primary nanoparticles, and to theoretically predict their potential for metal-enhanced luminescence applications. The morphology and structure of the resulting polydisperse nanoparticles were analyzed with transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDX). An increase in the average size from 15 to 26 nm and up to 7-time gain in the production rate with an increase in the energy density released on the electrodes were observed. The optical absorption spectra of the aluminum core-shell particles, both theoretically calculated through the Mie theory and experimentally obtained via spectrophotometry, exhibited plasmon resonance maxima in the deep ultraviolet range, with wavelengths spanning from 208 to 237 nm. Simulations of plasmon-enhanced fluorescence indicated a strong coupling of individual emitters to the plasmonic mode of produced aluminum nanoparticles and showed the enhancement factor ranging from 2 to 85 times, which depended on the particle size distribution, the quantum yield of the phosphor, the metal-emitter distance, and the excitation wavelength. The findings highlight that the produced polydisperse aluminum nanoparticles enhance emitter performance in the UV range, providing prospects for advancing optoelectronic devices.